A CONCEPÇÃO DE GRAMÁTICA E DE ENSINO DE GRAMÁTICA QUE EMERGE DA OBRA “A GRAMÁTICA DO PORTUGUÊS REVELADA EM TEXTOS” NEVES (2018) - SILVA, Thaiza Oliveira da (Universidade Federal do Oeste do Pará, 2022)
Linguistics, when constituted as a science, in the beginning of the 20th century, does not have its research focus turned to teaching. Despite this, at the end of the same century, a movement of grammar production began, which shows a certain concern with language teaching, since, in general, language teaching in schools is based on the knowledge left as a legacy by grammatical tradition. The objective of this work is to understand this movement of grammar production by linguists and what implications it has for teaching Portuguese in school. This work is part of a subproject, entitled “Analysis of grammars written by Brazilian linguists”, linked to the project “Language, grammar, variation and teaching”, developed since 2017 by the Linguistics Study Group of Western Pará – Gelopa. This subproject has four guiding questions: what is grammar?; what is teaching grammar?; why teach grammar?; and how to teach grammar?. This research aimed to answer these questions, starting from the analysis of the concept of grammar and grammar teaching that emerges from the work “A Gramática do Português Revelada em Textos” (GPRT), by Brazilian linguist Maria Helena de Moura Neves, published in 2018. This bibliographic research started, firstly, from four works by this author (NEVES, 2002; 2012; 2013; 2014), in order to verify the convergence or not of the author between her works and her grammatical production, besides serving as a support for the analysis of GPRT. Thus, according to the GPRT, grammar is an adaptable system and sensitive to the pressures of use, therefore adjustable; and to teach grammar is to look at the language and its interrelations in a reflexive way. For the author, grammar teaching that is not based on the reflection of language functions, is not a meaningful teaching for students. Grammar teaching must be related to showing how it organizes relationships, produces meanings and pragmatic effects within a context and, according to the author, grammar teaching should not be dissociated from language experiences, that is, to reflect on the language, one must take into account the context in which that text was produced.